(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
- Anthropogenic and population increase in the River In china river basin and coastal regions have placed great pressure upon that East China Sea (ECS) ecology. Poor resource stewardship and short-term economic goals have resulted in significant environmental degradation, presenting a danger to coastal communities’ health and well-being. Nitrogen, salt, tar hydrocarbons, organic detritus, and heavy metals are the primary contaminants. Nutrients cause eutrophication in marine and estuarine habitats, resulting in red tides. The decline of the River Basin does have a direct influence on the ECS’s aquatic environment. Stable current from the canal, along with tidal salty water in the estuary and sediment burdens from the river, prevents ocean degradation in the floodplain and its surrounding coastal region. This base would be altered by large-scale water transfer and dam development in the Yangtze River. The ECS must protect the environment by counteracting harmful processes. Integrating human and ecological decision-making is the most challenging problem. To address these challenges, a deeper knowledge of the social factors that generate environmental stresses is required. International cooperation will significantly aid development, especially in terms of financial, technological, scientific, and people resources.